Analysis of IDX-MES BUMN17 stocks using capital asset pricing - Muhammad Arifuddin; M Firdaus (Jurnal Ekonomi, 2024)
The purpose of this study is to analyze the CAPM method as the basis for the IDX-MES BUMN 17 share investment decision in January 2021-December 2022. The type of research in this study is quantitative research. The sampling technique used is purposive sampling. The sample in this research were 14 stocks on the IDX-MES BUMN 17 index with several criteria. To assess stock efficiency by comparing actual return (Ri) and expected return (Rj) and using the Security market Line (SML). The results of this study indicate there are 2 stocks including efficient stock, namely PGAS & PTPP. These shares have a value Ri>E(Rj), β>1 and based on Security market Line (SML) area. The investment decisions that investors make are to buy the stock.